Penafsiran Buya Hamka dan Quraisy Syihab Tentang Logika Berdebat Nabi Ibrahim - Qonitah Hafidzah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
In everyday life, a person is often faced with situations that cause debate among each other, both small and large debates. Therefore, lessons on how to argue well should be studied, especially for preachers, who will preach Islam to the wider community. If a preacher does not have the ability to express opinions, then the opinions or suggestions he gives, cannot give satisfactory results. One of the lessons that we can study about this is the story of the debate of the Prophet Ibrahim with his people which is explained in the Qur'an AL-Anbiya'verse 51-56. In reviewing the story, the writer uses a comparative method between the commentator Buya Hamka and Quraish Syihab, which is described descriptively, starting from the vocabulary of the verse, the commentator's explanation of the verse, ending with an explanation of the similarities, as well as the differences between the two commentators. The similarity of the points contained in Tafsir Al-Azhar with Tafsir Al-Misbah regarding this are: the gift that Allah has given him in the form of clarity of thought, enabling him to find the truth even though he is in the dark of disbelief, firmness in speech, accompanied by intelligent mind in taking action, so that it can influence the mind of the listener, or the interlocutor. Coupled with the courage of a young man in upholding the truth, without fear even though he has to fight against the authorities, is one of the keys to success in debating. The differences found between the two commentators are not too significant, only regarding the inclusion of references that are included.